2000
DOI: 10.1359/jbmr.2000.15.12.2443
|View full text |Cite
|
Sign up to set email alerts
|

Circannual Rhythms and Interactions of Vitamin D Metabolites, Parathyroid Hormone, and Biochemical Markers of Skeletal Homeostasis: A Prospective Study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
1
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 49 publications
9
81
1
4
Order By: Relevance
“…The relatively small inter-day variation in 25OHD may be predominantly attributable to its longer biological half-life in blood, in addition to the gradual release of vitamin D from skin and fat cells; whereas variation in intact PTH was larger due to its shorter half-life. In contrast, the lack of a clear seasonal variation in 1α ,25(OH) 2 D is consistent with several previous studies [28][29][30][31] , but contradicts a few studies which did report seasonal variation 19,32) . In our subjects, seasonal variation may have been attenuated by inter-day variation in 1α ,25(OH) 2 D, as it is well known that 1α ,25(OH) 2 D synthesis is strictly regulated by PTH, calcium, and phosphorous.…”
Section: Discussionsupporting
confidence: 85%
“…The relatively small inter-day variation in 25OHD may be predominantly attributable to its longer biological half-life in blood, in addition to the gradual release of vitamin D from skin and fat cells; whereas variation in intact PTH was larger due to its shorter half-life. In contrast, the lack of a clear seasonal variation in 1α ,25(OH) 2 D is consistent with several previous studies [28][29][30][31] , but contradicts a few studies which did report seasonal variation 19,32) . In our subjects, seasonal variation may have been attenuated by inter-day variation in 1α ,25(OH) 2 D, as it is well known that 1α ,25(OH) 2 D synthesis is strictly regulated by PTH, calcium, and phosphorous.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, 25-OHD represents the sum of vitamin D intake and dermal production [85]. Serum 25-OHD levels show a significant response to both sun exposure, as evidenced by the seasonal variation of levels, as well as to vitamin D supplementation [81,[86][87][88][89][90][91].…”
Section: -Hydroxy Vitamin D and 125-dihydroxy Vitamin Dmentioning
confidence: 99%
“…Table 7). With the exception of one small early study using a first generation assay [58], all studies identified reported a relative decrease in PTH concentration in summer and an increase in winter [54][55][56][57]. Studies undertaken with second generation assays suggested the difference between mean winter and summer concentrations was < 1 pmol/L [57,59].…”
Section: We Recommend Edta Plasma Samples For Pth Measurement Should mentioning
confidence: 99%